Fiscal Resilience to Natural Disasters : Lessons from Country Experiences - OECD; World Bank (OECD: Paris, 2019)
Large-scale catastrophic and smaller recurrent disasters generate considerable economic losses. Over the past thirty years, damages from major disasters have increased significantly. In the last ten years alone, both high-income and fast-growing middle-income economies have experienced an estimated 1.2 trillion US dollars in economic costs from disruptive shocks due to hazards such as storms or floods. The costs of disasters are often largely shouldered by governments, particularly where insurance coverage for these costs is limited. Often governments are not only responsible for the costs related to restoring public assets and services, but are also asked to provide financing for other explicit and implicit commitments made prior to a disaster. The costs that disasters impose on governments, and ultimately on taxpayers should be considered contingent liabilities or, when disasters lead to reductions in public revenues, contingent revenue losses. These expenses and revenue losses arise only if an uncertain event, such as a disaster, actually happens. Disaster-related contingent liabilities are one type of government contingent liability. This report presents the findings of a comparative study that assesses how effectively governments manage disaster-related contingent liabilities, and the potential fiscal risks arising from them, within public finance frameworks. The report documents and compares the policies and practices of a set of nine selected middle- and high-income economies focusing on their response to and plans for disasters from a public financial perspective. Economies were selected on the basis of their exposure to and regular experience of natural disasters, and with the aim of including economies of different sizes and fiscal capacity. Part 1 of the report first describes the economic impacts, and more specifically the fiscal impacts, arising from disasters in the selected economies. The nine detailed case studies are included as part 2 of the report.